Pengaruh Gender, Tingkat Pendidikan, dan Pengalaman Kerja Terhadap Love of Money pada Kantor Akuntan Publik di Bali - Lidia Rante Ledatu; Rai Gina Artaningrum; Luh Diah Citra Resmi Cahyadi (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2022)
Abstrak Tujuan dari penelitian ini ialah mengetahui sejauh apa pengaruh love of money yang meliputi gender, tingkat pendidikan, serta pengalaman kerja bagi love of money pada akuntan publik di Bali. Teknik sampling yang dipakai yakni purposive sampling terhadap spesifikasi auditor yang telah berjasa diatas 1 tahun dengan total populasi berjumlah 106 dan sampel yang diambil sebesar 70 auditor. Pengumpulan data dilakukan dengan memakai data primer melalui observasi dan wawancara, disisi lain teknik analisis yang dipakai yakni analisis regresi berganda. Pengujian analisis data pada penelitian ini memakai SPSS (Statistical Packgae for teh Social Sciences. Dari hasil analisis diperoleh bahwasanya pengaruh Gender, Tingkat Pendidikan dan Pengalaman Kerja tidak memiliki pengaruh terhadap love of money pada kantor akuntan publik di Bali Abstract Money is an essential aspect of daily life for carrying out transactions, and the concept of "Love of Money" is psychological literature that measures how much a person loves money. This evaluation directs to influence the proportion to which gender, education level, also work experience influence the love of money in public accounting firms in Bali. This contemplate was conducted in 2021 at a universal accounting trueheart in Bali that has joined IAPI. This study's population was 106 auditors, and the sample size was 70 auditors. Ppurposeful distribution was euphemistic pre-owned therein glance at with criteria for auditors who had worked for bounteous than a gathering. This study's data source was primary data. SPSS was euphemistic pre-owned to psychoanalyse investigation collections in this contemplate (Statistical combination for Tea collective Sciences). aggregate one-dimensional retrogression was euphemistic pre-owned to psychoanalyse the data. On the authority of the research’s findings, the influence of Gender, Education Level, and Work Experience does not affect on the love of money in Bali's public accounting firms.